Minocycline does not evoke anxiolytic and antidepressant-like effects in C57BL/6 mice - Vogt, Miriam A.; Inta, Ioana; Gass, Peter; Inta, Dragos (Behavioural brain research, 2016)
Minocycline is a broad-spectrum tetracycline antibiotic with multiple actions, including anti-inflammatory and neuroprotective effects, that was proposed as novel treatment for several psychiatric disorders including schizophrenia and depression. However, there are contradictory results regarding antidepressant effects of minocycline in rodent models. Additionally, the possible anxiolytic effect of minocycline is still poorly investigated. Therefore, we aimed to clarify in the present study the influence of minocycline on behavioral correlates of mood disorders in standard tests for depression and anxiety, the Porsolt Forced Swim Test (FST), Elevated O-Maze, Dark-Light Box Test and Openfield Test in adult C57BL/6 mice. We found, unexpectedly, that mice treated with minocycline (20-40mg/kg, i.p.) did not display antidepressant- or anxiolytic-like behavioral changes in contrast to mice treated with diazepam (0.5mg/kg, anxiety tests) or imipramine (20mg/kg, depressive-like behavior). These results are relevant for future studies, considering that C57BL/6 mice, the most widely used strain in pharmacological and genetic animal models, did not react as expected to the treatment regime applied.
Gesehen am 27.03.2019
Available online 14 December 2015